2023
DOI: 10.3390/plants12244177
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Epigenetic Changes in A. thaliana Calli: Impact of HDAC Inhibitors

Pavlína Pírek,
Karolína Kryštofová,
Ingrid Kováčová
et al.

Abstract: The ability for plant regeneration from dedifferentiated cells opens up the possibility for molecular bioengineering to produce crops with desirable traits. Developmental and environmental signals that control cell totipotency are regulated by gene expression via dynamic chromatin remodeling. Using a mass spectrometry-based approach, we investigated epigenetic changes to the histone proteins during callus formation from roots and shoots of Arabidopsis thaliana seedlings. Increased levels of the histone H3.3 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Additionally, four articles are dedicated to epigenetic changes and plant proteins. Pírek et al [ 7 ] used a mass spectrometry-based approach to investigate epigenetic changes in histone proteins during callus formation in the roots and shoots of Arabidopsis thaliana seedlings. The results showed that an early callus derived from seedling shoots and roots showed specific epigenetic patterns, whereas a long-term cultured callus was homogenized.…”
mentioning
confidence: 99%
“…Additionally, four articles are dedicated to epigenetic changes and plant proteins. Pírek et al [ 7 ] used a mass spectrometry-based approach to investigate epigenetic changes in histone proteins during callus formation in the roots and shoots of Arabidopsis thaliana seedlings. The results showed that an early callus derived from seedling shoots and roots showed specific epigenetic patterns, whereas a long-term cultured callus was homogenized.…”
mentioning
confidence: 99%